The Auditory Setting Environmental Sounds in Film and Media Arts. - Chattopadhyay, Budhaditya (Music and the moving image., 2021)
The Auditory Setting introduces and investigates how narrative and a sense of place are constructed in film and media arts through the reproduction and mediation of site-specific environmental sounds, or 'ambience'.